Analytical study of operating modes of RF ion funnels in the gas dynamic interfaces of tandem triple-quadrupole mass-spectrometers - Sysoev Alexey; Berdnikov Alexander; Masyukevich Sergey; Solovyev Konstantin; Krasnova Nadezhda (St. Petersburg Polytechnical University Journal: Physics and Mathematics, 2023)
The article considers analytical models of high-frequency electric fields which can be used effectively for fast, high-quality simulation of ion flow focusing and transport processes in the radio-frequency funnels. In particular, the use of such devices in the design of a tandem three-quadrupole mass spectrometer increases the amount of ions collected in the forevacuum region of the gas-dynamic interface of the electrospray ion source. The cases of funnels with two- and four-phase electrical voltages (options I and II), as well as with amplitude-modulated electrical voltages providing a pseudopotential mode with an Archimedean wave (III) have been analyzed. As a result, the most preferable design turned out to be option III. The use of such analytical models makes it possible to test effectively promising options and thereby significantly reduce costs for the preliminary selection of a principal scheme of a device with specified characteristics, including similar cases of other mass spectrometric designs.